Current Priorities in Campus Recreation: A Multi-Institutional Study of Strategic Plans. Issue 1 (April 2019) - Lower-Hoppe, Leeann M.; Parietti, Megan L.; Czekanski, W. Andrew
Strategic planning is a proactive process of analyzing an organization to identify the organization's values, mission, vision, goals, and objectives. Within campus recreation, research has focused on the processes of strategic planning, without examining the distinct organizational strategies of individual departments. The purpose of the study was to examine the content and structure of strategic plans within campus recreation and identify major priorities across institutions as a means to inform campus recreation practice. To achieve this aim, document analyses were conducted on campus recreation strategic plans of five large universities (public and private) across the United States for content and structure. The data were categorized by prominent strategic planning components outlined in Haines's campus recreation assessment model, from which codes and themes emerged. A standard of excellence, service, and outcomes were identified as major priorities across institutions and strategic planning components. The results demonstrated an ineffective structure of goals and objectives, highlighting areas for improvement. Through empirical investigation, industry standards can be established to enhance quality programming in campus recreation.